Определение длительности оптимального по затратам энергии переходного процесса - Дудник, Алексей Валентинович (НТУ "ХПИ", 2007)
У статті розглянуто питання про пошук області існування оптимальних керуючих дій. Наведені аналітичні співвідношення для розрахунку тривалості оптимального по енергетичним витратам управління та алгоритма, який його втілює.

There is a way of optimal solution field searching is discussed in this paper. Several analytical equations are introduced here. These ones may be used to time of optimal power saving process calculation. Simultaneously, they let obtain an optimal algorithm number.
Keywords: энергоемкость продукции; потери энергии; алгоритмы управления; быстродействие; энергосбережение; приводы постоянного тока